O curso prolongado do movimento dos trabalhadores rurais Sem Terra no Ceará e o processo de formação política da juventude. - Veras., Clédia Inês Matos (2007)
The present dissertation examines the educational practices for the political education of the young people developed in the Long-run Course in the Landless Movement of Rural Workers (MST) of the state of Ceará. With the objective of investigating the educational process of the mentioned course in its politicalpedagogic principles and its relation to the Popular Education in a praxis dimension, the research, from the qualitative data survey by the means of projects analyses and life reports, tried to evaluate how the access to education and the political formation contributed to the change of the conception of world the adolescents of the MST have. The identification of these subjects demanded an understanding of their historical conditioning, having as a starting point the history of the right of land and the necessary practices and knowledge to stay there. The course of the rural struggles which generated the Landless Movement led to the necessity of a specific education to the technical and socio-cultural conditions of the rural area. In the political formation of the Landless people who compose the Landless Movement, their speech mention the Long-run Course as a fundamental moment to every way of political participation, inside or outside the movement. It happens according to the proposal the movement presents to aggregate reflection and action, theory and practice, in a way to develop an epistemological curiosity to the elaboration of a critical knowledge of the rural workers.